Anti-cellulite and slimming effect of vacuum massage - a case study - Anna Baryluk; Magdalena Łuniewska; Wojciech Garczyński; Magdalena Gębska; Katarzyna Weber-Nowakowska (Journal of Education, Health and Sport, 2017)
Cellulite - local metabolic disease that begins deep in the subcutaneous tissue, refers to fat cells and microcirculation mainly in the hips, thighs and abdomen area. The mechanism of cellulite is strictly connected with impaired microcirculation. Swollen tissue compresses blood vessels causing disturbance of microcirculation in the skin and subcutaneous tissue, which in turn causes fat cells ischemia. One of the therapeutic methods used in the case of cellulite is a vacuum massage, which includes Chinese cupping massage, and glass bubbles. This type of anti-cellulite massage affects the skin nutrition by improving the circulatory and lymphatic systems. The case report concerned a woman aged 25, with a normal BMI (21 kg / m2), and apple obesity type (WHR 1.14), treated pharmacologically due to phenylketonuria, irregularly nourished with a low protein diet, but rich in vegetables, fruit and fluids. The study and observations period lasted 30 days, including 20 days of treatments conducted every other day (glass buble and buble gum by turns), and 10 days of total withdrawal from the vacuum massage, in order to exemine the long-term results. Each treatment began with vigorous rubbing and kneading the thighs in order to obtain congestion, and then the appropriate vacuum massage. The treatment time - 30 min. per thigh. During the study there were four thigh circuits measurements performed using the dipstick anthropometric as well as a photographic documentation completed in order to exemine the progress of treatment. The measurements and photographs were taken on the first day of the treatments, in the middle of the treatments, and at the end of the treatments also after 10 days of the massage withdrawal. The circuits measurements were collected in three different places. First directly on the patella and another two at a distance of 9 cm from the previous measurement in the cephalad direction. The greatest change in the circumference of the thigh was noted during the third measurement, after a series of 10 treatments. Visually, the cellulite decreased. Within 10 days after treatment cessation the effect of the reduced cellulite was satisfactory, but the thighs circuits measurements obtained the same value as it was before treatment. Based on the case description one can assume that the vacuum massage reduces the cellulite and also the body fat. The success of this massage is effective only with the systematic performance. An important factor is the intensity of performing the treatment, a prior preparation of the skin, and also an appropriate diet. In order to assess the effectiveness of vacuum massage there should be studies carried out on a larger number of patients.